Axitinib treatment in advanced RAI-resistant differentiated thyroid cancer (DTC) and refractory medullary thyroid cancer (MTC). Issue 4 (October 2017) - Capdevila, Jaume; Trigo, José Manuel; Aller, Javier; Manzano, José Luís; Adrián, Silvia García; Llopis, Carles Zafón; Reig, Òscar; Bohn, Uriel; Cajal, Teresa Ramón y; Duran-Poveda, Manuel; Astorga, Beatriz González; López-Alfonso, Ana; et al.
Abstract : Background: Axitinib, an antiangiogenic multikinase inhibitor (MKI), was evaluated in the compassionate use programme (CUP) in Spain (October 2012–November 2014). Subjects and Methods: 47 patients with advanced radioactive iodine (RAI)-refractory differentiated thyroid cancer (DTC, n  = 34) or medullary thyroid cancer (MTC, n  = 13) with documented disease progression were treated with axitinib 5 mg b.i.d. The primary efficacy endpoint was objective response rate (ORR) by Response Evaluation Criteria In Solid Tumors (RECIST) v1.1. Progression-free survival (PFS) and adverse events (AEs) were secondary objectives. Regulatory authorities validated the CUP, and all patients signed informed consent form. Results: Axitinib was administered as first-line therapy in 17 patients (36.2%), as second-line in 18 patients (38.3%) and as third/fourth-line in 12 patients (25.5%). With a median follow-up of 11.5 months (0–24.3), ORR was 27.7% (DTC: 29.4% and MTC: 23.1%) and median PFS was 8.1 months (95% CI: 4.1–12.2) (DTC: 7.4 months (95% CI: 3.1–11.8) and MTC: 9.4 months (95% CI: 4.8–13.9)). Better outcomes were reported with first-line axitinib, with an ORR of 53% and a median PFS of 13.6 months compared with 16.7% and 10.6 months as second-line treatment. Twelve (25.5%) patients required dose reduction to 3 mg b.i.d. All-grade AEs included asthenia (53.2%), diarrhoea (36.2%), hypertension (31.9%) and mucositis (29.8%); grade 3/4 AEs included anorexia (6.4%), diarrhoea (4.3%) and cardiac toxicity (4.3%). Conclusion: Axitinib had a tolerable safety profile and clinically meaningful activity in refractory and progressive thyroid cancer regardless of histology as first-line therapy. To our knowledge, this is the first time that cross-resistance between MKIs is suggested in thyroid cancer, highlighting the importance of prospective sequential clinical studies.